Investment and Interventions to Improve the Quality of Education Systems. - Chi, Jin.; Vélez Bustillo, Eduardo ([Place of publication not identified] : Routledge, 2021)
Quality improvement is a major current goal of Education in China and this will be achieved through overall quality improvement of the education system as a whole, a situation that is also the case across the world. Deploying a cost-benefit analysis and multidisciplinary perspectives from education, economics, neurocognition, gender studies, child development, and international development, this book presents a range of critical interventions in education development and investment that have proven to be effective in many countries around the world. The book draws on theoretical and practical experience in the field of education investment and analyses key issues in China's early childhood education, early reading, girls' education, brain science application in international education, small-scale schools in low income areas and teacher education. Students and scholars of education and development and Chinese education will benefit from this title.
1. Why to Invest in Education: An Economic Perspective. 2. Physical Conditions of Schools and Education Outcomes. 3. Investment in Early Childhood Development: Observations from Empirical Evidence. 4. Vision Before Comprehension: Neglected Variables Affect the Performance of Low-income students. 5. Girls' Education: Why to Invest and What Works. 6. Improving Teaching and Learning in Low-income Schools: Innovation and Implications for Escuela Nueva. 7. How Can the Education Systems Get Quality Teachers?
Keywords: EDUCATION / Educational Policy & Reform / General; EDUCATION / Evaluation; EDUCATION / Finance; Education -- China; School improvement programs -- China; Education and state -- China; Early childhood education -- China; Girls -- Education -- China